Development of the Chinese financial system and reform of Chinese commercial banks - Luo, Dan (2010)
Comprehensive economic reform in China from 1978 has introduced profound restructuring of its financial system, in particular the banking sector. Recent initiatives have focused on ownership transformation via foreign participation and stock listing. China's stock markets have reacted highly positively to the Initial Public Offering (IPO) of Chinese commercial banks. As stock listing has been considered as an effective tool to enhance the corporate governance of the firms, a case study using China Construction Bank (CCB) had been conducted to get a more detailed understanding of in what aspects had the corporate governance of the listed banks been enhanced after IPO? By comparing the annual reports of CCB from 1999 to 2008, I found that the bank had made quite profound and comprehensive changes since its IPO in 2005. In all major areas required by the corporate governance principles, the CCB had displayed a very high level of compliance although flaws in some fundamental aspects still existed.